The role of the community in the development of local wisdom-based tourism in Meat tourism village, Tampahan District, Toba Regency - Sitepu, Ayu Ansari; Sirait, Loly Surya; Khairi, Nur Khafiza (Journal of Commerce, Management, and Tourism Studies, 2023)
The Ministry of Tourism has acknowledged that Lake Toba in North Sumatra is one of Indonesia's top five destinations of high priority. This study aims to identify various forms of local wisdom that exist in the Meat (Desa Meat) tourism village and analyze the role of the community in tourism development there. The research method used is qualitative analysis through observation and literature study. Sources of data used in this research include books, journals, websites, and other relevant references related to the theme of this research. Meat village which is located in the vicinity of Lake Toba, has also been designated as one of the tourism development areas. The reason behind the appointment is because this village not only has abundant natural beauty, but also manages to maintain its distinctive artistic and cultural elements. Research has proven that Meat village has a tourism concept that is based on local wisdom, in which the local community is actively involved in developing tourism through the production of woven yeast hotang cloth. Besides being valuable as part of human creativity, the potential for this local wisdom also has significant economic value. The development of a tourism village that focuses on local wisdom like this can be used as an example for other villages interested in developing the concept of rural tourism.